Marriage Application Procedure Abroad: A Qualitative Study at Negeri Sembilan Islamic Religious Affairs Department (JHEAINS) - Shahrom, Nur Fatin Nabilah; Aris Fezul, Ahmad Nasrullah; Ismail, Noraini; Abu Bakar, Marina; Ali, Zuraimy (Online Journal of Research in Islamic Studies, 2025)
Marriage in Islam is a highly encouraged Sunnah for all Muslims. However, the evolution of time has necessitated that every marriage undergoes several procedures to ensure its legal validity in a given country. The issue of unregistered marriages abroad among Malaysian Muslim citizens has been increasing day by day. This phenomenon is attributed to several factors, including a lack of knowledge about marriage application procedures abroad, polygamy without official permission, the absence of family consent, and the complexity of marriage registration procedures. Therefore, this article highlights a study on the marriage registration application procedures for local citizens marrying abroad, focusing on the Negeri Sembilan Islamic Religious Affairs Department (JHEAINS) as the research subject. This study adopts a qualitative research approach utilizing semi-structured interview techniques. An interview was conducted with a Marriage, Divorce, and Reconciliation Officer at JHEAINS to gather information regarding the marriage application procedures for Malaysian Muslim citizens abroad. The study found that marriage registration procedures abroad are divided into two categories which are marriages between Malaysian citizens that take place abroad and marriages between a Malaysian citizen and a foreign national abroad. The registration process involves the submission of 12 essential documents. The findings emphasize the importance of public awareness and understanding of marriage procedures to reduce instances of unauthorized marriages abroad. In conclusion, this article provides significant insights into the issue of overseas marriages and highlights the need for education and public awareness to ensure adherence to proper marriage procedures.